2021
DOI: 10.1038/s41598-021-83171-7
|View full text |Cite
|
Sign up to set email alerts
|

Association between solid fuel use and cognitive decline among middle-aged and elderly Chinese adults: a longitudinal study

Abstract: This study was conducted to investigate (1) the association between solid fuel use for cooking and cognitive function; (2) the moderating effects of gender and residential area on cognitive scores among solid fuel users; and (3) the effects of solid fuel use on cognitive decline among different gender and age subgroups in 2011–2018. A total of 5140 Chinese middle-aged and elderly participants were successfully followed for 7 years (2011–2018). Solid fuel use was self-reported as using solid fuel for cooking at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 44 publications
(32 reference statements)
0
6
0
Order By: Relevance
“…We created 10 replications and pooled the imputed results to account for the missing data using linear regression models. 36 Baseline data are described as frequencies (percentages) for categorical variables and means (SDs) for continuous variables. Baseline characteristics are summarised according to cooking fuel use, and the Χ 2 test (for categorical variables) or t-test (for continuous variables) was used to compare the differences in baseline characteristics among different fuel users.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We created 10 replications and pooled the imputed results to account for the missing data using linear regression models. 36 Baseline data are described as frequencies (percentages) for categorical variables and means (SDs) for continuous variables. Baseline characteristics are summarised according to cooking fuel use, and the Χ 2 test (for categorical variables) or t-test (for continuous variables) was used to compare the differences in baseline characteristics among different fuel users.…”
Section: Discussionmentioning
confidence: 99%
“…Question options included coal, crop residue, wood, natural gas, marsh gas, liquefied petroleum gas, electric, never cook and other fuels. 36 We excluded participants who never cooked and used other fuels. According to the health effects of fuel burning, 37 we defined cooking fuel as clean fuel (natural gas, marsh gas, liquefied petroleum gas, electric) and solid fuel (coal, crop residue and wood).…”
Section: Assessment Of Incidental Non-fatal Cvd Eventsmentioning
confidence: 99%
“…The figure drawing test asked the participants to successfully reproduce a picture of two overlapping pentagons shown by the interviewers. The respondents who successfully drew this picture received 1 point, but those who failed to draw it received no score [ 18 ]. Finally, the mental status score was defined as the sum of all 3 parts, ranging from 0 to 11 [ 19 ].…”
Section: Methodsmentioning
confidence: 99%
“…In addition, they were asked to recall the 10 words 5 min later (delayed recall) and were given 1 point for each word they recalled correctly. The score for episodic memory was equal to the average of the sum of immediate recall and delayed recall, ranging from 0 to 10 [ 18 ].…”
Section: Methodsmentioning
confidence: 99%
“…Indoor air pollution is responsible for ischemic heart diseases (27%), pneumonia (27%), chronic obstructive pulmonary diseases (20%), stroke (18%), and lung cancer (8%), accounting for approximately 4 million deaths worldwide [ 9 ]. In addition to physical health impairment, studies have suggested that indoor air pollution contributes to cognitive decline and may also result in mental disorders [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%